Applying Structural Equation Modeling to Explore the Intention to Use Midi Kriing App - Sangadji, Suwandi S.; Handriana, Tanti; Wisnujati, Nugrahini Susantinah; Karim, Sarbaini A. (Bright Publisher, 2024)
In the rapidly evolving digital landscape, the surge in e-commerce transactions underscores the need for innovative strategies to enhance user satisfaction, trust, and sustainable app usage. This research focuses on the Midi Kriing App, operated by PT Midi Utama Indonesia Tbk, a key player in the e-commerce industry. The study aims to bridge knowledge gaps by investigating factors influencing user intention, specifically e-service quality and e-trust, and their impact on user satisfaction. Employing a quantitative approach with an associative design, data was gathered from 190 Midi Kriing App users in Surabaya, Indonesia. Structural Equation Modeling (SEM), particularly Partial Least Squares (PLS) in SmartPLS, was utilized to explore relationships between variables. Research findings indicate that e-service quality and e-trust significantly impact user satisfaction, with a p-value of 0.00. Similarly, user satisfaction significantly influences the intention to use the Midi Kriing App, with a p-value of 0.00. Among these hypotheses, the statistical t-value of user satisfaction with the intention to use the Midi Kriing App, at 9.871, is higher than the relationship between e-service quality and e-trust with user satisfaction. Nevertheless, these hypothesis tests confirm statistically significant relationships, supporting the reliability and significance of each construct's measurement instruments. In conclusion, this research emphasizes the pivotal role of satisfaction in its relation to e-service quality, e-trust, and the intention to use the Midi Kriing App. Managerial implications stress the importance of enhancing these factors to drive app usage. Improving e-service quality can be achieved through active efforts such as enhancing responsiveness, reliability, and user-friendliness. Similarly, building e-trust involves securing user data and providing a positive user experience.